Modal evaluation of fluid volume in spacecraft propellant tanks - Mathe, Steven; Anderson, KelliAnn; Bakkum, Amber; Lubick, Kevin; Robinson, John; Weiland, Danielle; Werlink, Rudy; Crosby, Kevin M. (Proceedings of the Wisconsin Space Conference, 2012)
Propellant mass-gauging in unsettled (sloshing) fluids is an important and unsolved problem in spacecraft operations and mission design. In the present work, we demonstrate the efficacy of the experimental modal analysis technique in determining the volume of fluid present in model spacecraft propellant tanks undergoing significant sloshing. Using data acquired over approximately 37 minutes of time in zero-gravity conditions provided over two years of parabolic flights, we estimate the resolution of the technique at low tank fill-fractions where other mass-gauging techniques are known to fail.Â